1990
DOI: 10.1128/mcb.10.2.510
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometry of G protein subunits affects the Saccharomyces cerevisiae mating pheromone signal transduction pathway.

Abstract: The Saccharomyces cerevislae GPA1, STE4, and STE18 genes encode products homologous to mammalian G-protein a, ,, and y subunits, respectively. All three genes function in the transduction of the signal generated by mating pheromone in haploid cells. To characterize more completely the role of these genes in mating, we have conditionally overexpressed GPAI, STE4, and STE18, using the galactose-inducible GAL] promoter. Overexpression of STE4 alone, or STE4 together with STEJ8, generated a response in haploid cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
116
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 53 publications
(41 reference statements)
6
116
0
Order By: Relevance
“…15Dau is a MATa derivative of BF264-15D (18). Temperature-sensitive and deletion mutants used were as follows: cdc4-1 leu2 ura3; cdc4-1 GAL1: CDC6(URA3) leu2 ura3; cdc4-1 sic1::URA3 leu2 ura3; cdc34-2 ura3 his3; cdc34 -2 sic1::URA3 leu2 ura3; and cdc6::kanMX4 GAL1:CDC6 (URA3).…”
Section: Methodsmentioning
confidence: 99%
“…15Dau is a MATa derivative of BF264-15D (18). Temperature-sensitive and deletion mutants used were as follows: cdc4-1 leu2 ura3; cdc4-1 GAL1: CDC6(URA3) leu2 ura3; cdc4-1 sic1::URA3 leu2 ura3; cdc34-2 ura3 his3; cdc34 -2 sic1::URA3 leu2 ura3; and cdc6::kanMX4 GAL1:CDC6 (URA3).…”
Section: Methodsmentioning
confidence: 99%
“…Integration of the mutant allele into the chromosome eliminates variability in plasmid copy number that affects protein expression levels. The pheromone response pathway is exquisitely sensitive to changes in Gpa1p expression (Cole et al, 1990;Kang et al, 1990). Studies of other GPA1 mutations have revealed different phenotypes when expressed on a centromere-based plasmid instead of the chromosomal locus (Miyajima et al, 1989;Kurjan et al, 1991).…”
Section: Gpa1p Is Dually Myristoylatedmentioning
confidence: 99%
“…Plant TRX expression in yeast cells was achieved using either the inducible Ycp2 shuttle vector (Cole et al, 1990) or the constitutive pFL61 vector (Minet et al, 1992). Each plant TRX was amplified from the corresponding full-length cDNA by PCR using specific pairs of oligonucleotides designed to introduce either MluI (5#)/BamHI (3#) or NotI (5#)/NotI (3#) sites necessary for cloning into Ycp2 and pFL61 vectors, respectively (MluIhN/PeahC and NotIhN/NotIhC to amplify and clone h1 ORF; MluIh2N/Peah2C and NotIh2N/NotIh2C for h2 cloning; Table I).…”
Section: Heterologous Complementation Analysismentioning
confidence: 99%